2007
DOI: 10.1007/s11430-007-0108-7
|View full text |Cite
|
Sign up to set email alerts
|

Present-day horizontal deformation status of continental China and its driving mechanism

Abstract: Based on velocity data of 933 GPS sites and using the methods of Ordinary Kriging interpolation and shape function derivation, this study has obtained the strain rate field of continental China in the spherical coordinates. In comparison with previous research results, it is found that such a strain rate field can be described by both the continuous deformation and block motions in the continent. The Tibetan Plateau and Tianshan region are characterized by continuous deformation which is distributed across the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…There is no obvious evidence showing that the orientation of principal stress could have changed nearly 90° from the start to the end of the Wenchuan earthquake fault within approximately 300 km. The tectonic stress field derived by previous works undertaken before the Wenchuan earthquake (e.g., Chen, ; Deng et al, ; Wang et al, ) suggested that the tectonic stress field does not change significantly in the spatial region hosting the Wenchuan earthquake. Thus, in this work, we use a homogeneous tectonic stress field in the entire calculation volume, except that the stress varies with depth, considering depth‐dependent lithostatic pressure.…”
Section: Modelmentioning
confidence: 89%
See 1 more Smart Citation
“…There is no obvious evidence showing that the orientation of principal stress could have changed nearly 90° from the start to the end of the Wenchuan earthquake fault within approximately 300 km. The tectonic stress field derived by previous works undertaken before the Wenchuan earthquake (e.g., Chen, ; Deng et al, ; Wang et al, ) suggested that the tectonic stress field does not change significantly in the spatial region hosting the Wenchuan earthquake. Thus, in this work, we use a homogeneous tectonic stress field in the entire calculation volume, except that the stress varies with depth, considering depth‐dependent lithostatic pressure.…”
Section: Modelmentioning
confidence: 89%
“…Thus, in this work, we use a homogeneous tectonic stress field in the entire calculation volume, except that the stress varies with depth, considering depth‐dependent lithostatic pressure. The orientation of the maximum horizontal compressional stress σ H is set to N280°E (Figure ), according to various studies on the tectonic stress state in the Longmen Shan region (Chen, ; Deng et al, ; Wang et al, ). Although there are some works suggesting the stress filed maybe rotate along the Beichuan fault (Gao et al, ), we use the simple uniform stress filed (with the maximum horizontal compressional stress pointing to N280°E [Figure ]) along the fault plane.…”
Section: Modelmentioning
confidence: 99%
“…Based on our 3‐D electrical model, combining with GPS [ Liang et al, ; Chen , ], thermal structure [ Wei and Zang , ], and seismic survey results [ Bao et al, ], a concept model is proposed to interpret geodynamic process the Ludian earthquake (Figure ). The SSE trending motion of the CDB defines the dominant left‐lateral slip of the NW trending faults in Ludian earthquake region.…”
Section: Discussionmentioning
confidence: 99%
“…However, both the field investigation and focal mechanism solution indicate that the study region has a few tensional deformation [ Xu et al, , ; Li et al, ]. The results of the dilatation strain calculated from GPS data also demonstrate that the Ludian earthquake occurred in a tensional deformation area [ Chen , ]. The SSE trending motion of the CDB defines the dominated deformation characteristics of the study region, namely, NW trending left‐lateral slip and NE trending right‐lateral slip.…”
Section: Introductionmentioning
confidence: 99%
“…(d) The seismogenic structure is neither the Cangdong fault nor the Douhe fault in the shallow crust (J. Xu & Ji, 2015), but rather a steep fault buried in the deep crust under the earthquake area (G. D. Liu, 1994;B. J. Liu et al, 2011;C.…”
Section: Discussionmentioning
confidence: 99%